Edge of empires : a history of Georgia - Rayfield, Donald, 1942- (Reaktion Books, 2012)
This is a comprehensive history of Georgia focusing not only on the post-Soviet era but on the full sweep of its turbulent past. The book describes Georgia's complex struggles with the many empires which have tried to control, fragment or even exterminate the country.